Anais Do XX Congresso Brasileiro De Engenharia Química 2015
DOI: 10.5151/chemeng-cobeq2014-1173-20666-147155
|View full text |Cite
|
Sign up to set email alerts
|

USE OF BROCCOLI (Brassica oleracea italica) LEAVES POWDER TO PRODUCE FRESH PASTA

Abstract: -Broccoli is a vegetable usually consumed by the population as a source of bioactive compounds such as carotenoids and tocopherols. However, the broccoli processing mainly uses the flowers, remaining the leaves and stalks as by-products. This work used dried broccoli leaves powder to enrich fresh pasta, and compared its sensory and technological characteristics with pasta enriched with spinach powder. The levels of lutein and β-carotene in broccoli flower and leaves were also quantified. Lutein and β-carotene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
5
1
0
Order By: Relevance
“…Similar results were reported by Islas-Rubio et al (2014). Results of pasta with SF and EF were in agreement with those presented by Cemin et al (2014). Results of pasta with SF and EF were in agreement with those presented by Cemin et al (2014).…”
Section: Colour Characteristicssupporting
confidence: 91%
See 4 more Smart Citations
“…Similar results were reported by Islas-Rubio et al (2014). Results of pasta with SF and EF were in agreement with those presented by Cemin et al (2014). Results of pasta with SF and EF were in agreement with those presented by Cemin et al (2014).…”
Section: Colour Characteristicssupporting
confidence: 91%
“…These results showed that samples 0% have a yellowish tint with positives values of (a*) and (b*) parameters ( Table 2). Results of pasta with SF and EF were in agreement with those presented by Cemin et al (2014). Hence, pastas supplemented with SF and EF have a greenishyellowish tint.…”
Section: Colour Characteristicssupporting
confidence: 89%
See 3 more Smart Citations